Preparation And Characterization Of Graphene Oxide - Zinc Oxide Nanocomposite In Degradation Of Phenanthrene From Aqueous Solutions - Chauhan, Husn Ara (2022)
Environmental concerns have arisen due to the persistent nature and carcinogenicity of polycyclic aromatic hydrocarbons (PAHs). Skin, lung, pancreatic, oesophageal, bladder, colon, and female breast cancer are only some of the organs that have been linked to long-term PAH exposure. It has been suggested that being exposed to PAH also raises the odds of developing lung cancer. Thus, the use of nanocomposites with high-efficiency properties is necessary. This study used the doping approach to successfully construct a nanocomposite photocatalyst based on graphene oxide (GO) and zinc oxide (ZnO). The nanocomposites were investigated by Fourier transform infrared (FTIR) spectroscopy, UV-Visible diffuse reflectance spectroscopy (UV-Vis DRS), X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM) with energy dispersive X-ray (EDX), transmission electron microscopy (TEM), Brunaeur-Emmett-Teller (BET). The photocatalytic activity of synthesized nanocomposites was tested in phenanthrene deterioration as a precursor of contaminants in water. At 6.8 pH, the GO/ZnO nanocomposite showed excellent ability to degrade 25 ppm of phenanthrene (86.06%) in 120 minutes under UV-Visible light exposure followed by commercial ZnO (62.84%), GO/ZnO in the dark with stirring (47.40%), GO/ZnO without stirring (40.28%), and photolysis (no photocatalyst) (15.56%).